Noun Derivations in -Ost in Prekmurje Sermons and Their Lexicographic Documentation in Pleteršnik’s Dictionary - Zver, Nina (ZORA 160: Imenitnost slovenščine sto let po Pleteršniku, 2026)
The article examines nominal derivatives in -ost in Prekmurje sermons from the Berden collection, especially in the sermons of Jožef Horvat, Franc Ivanocy, Franc Gašpar, and other authors from the late nineteenth and early twentieth centuries. It focuses on lexemes with religious connotations, i.e. those denoting key concepts of Christian belief, ecclesiastical practice, and religious experience, or fulfilling a distinctly moral and ethical function in sermon discourse. The analysis com-bines word-formational, semantic, and lexicographic perspectives and examines their being documented in Pleteršnik’s dictionary and in the Slovar stare knjižne prekmurščine.